Voltage combined with pace mapping is simple and effective for ablation of noninducible premature ventricular contractions originating from the right ventricular outflow tract. Issue 12 (December 2016) - Wang, Zefeng; Zhang, Heping; Peng, Hui; Shen, Xuhua; Sun, Zhijun; Zhao, Can; Dong, Ruiqing; Gao, Huikuan; Wu, Yongquan
Abstract : Background: Premature ventricular contractions (PVCs) from the right ventricular outflow tract (RVOT) can resist conventional mapping strategies. Studies regarding optimal mapping and ablation methods for patients with noninducible RVOT‐PVCs are limited. We retrospectively evaluated the efficacy and safety of a novel mapping strategy for these cases: voltage mapping combined with pace mapping. Hypothesis: Methods: We retrospectively included symptomatic patients (n = 148; 76 males; age, 44.5 ± 1.4 years) with drug‐refractory PVCs originating from the RVOT, who underwent radiofrequency catheter ablation (RFCA), and stratified them as Group 1 and Group 2. Group 1 patients had noninducible RVOT‐PVCs, determined after programmed stimulation, burst pacing, and isoproterenol infusion (n = 21; 12 males; age, 39.5 ± 10.8 years). Group 2 patients had inducible PVCs. Group 1 patients were subjected to voltage mapping combined with pace mapping; Group 2 underwent conventional mapping. In all patients prior to RFCA, detailed 3‐dimensional electroanatomic voltage maps of the RVOT were obtained during sinus rhythm using the CARTO system. Results: Patients from both groups had similar success and complication rates associated with the RFCA. In Group 2, 89% (113/127) experienced the earliest and the successful ablation points in the voltage transitional zone. During the follow‐up (36 ± 8 months), patients from both groups suffered similar rates of PVC relapse (2/21 and 7/127, respectively; P = 0.826). Conclusions: Voltage mapping combined with pace mapping is effective and safe for patients with noninducible RVOT‐PVCs determined by conventional methods.